Underwater hyperspectral imaging system for deep-sea exploration - Xue, Qingsheng; Li, Hui; Lu, Fengqin; Bai, Haoxuan (Frontiers in Physics, 2022)
As a technology that combines spectral technology and imaging technology, hyperspectral imaging technology can obtain the spectral and spatial information about the targets effectively. Hence, the underwater hyperspectral imaging technology has a fast development since it was first used underwater. Many kinds of hyperspectral imagers used for underwater detection at different depths were developed. However, the underwater hyperspectral imagers used at deep sea were rarely reported while the required detection depth increased. To satisfy the deep-sea exploration requirements, an underwater hyperspectral imaging system was designed. An optical system with a low F-number and a compact structure was first designed. The F-number of the system is 2.5. The focal length of the objective lens is 25 mm, and the field of view of the objective lens is 35.2°.The wavelength range of the system is from 400 to 1000 nm, and the spectral resolution of the spectrometer is better than 3 nm. The instrument cabin and other structures for waterproofing were designed. A minicomputer used for control communication, data acquisition, and processing was equipped in the actual system. The isolation performance and imaging quality were tested in the laboratory environment. According to the test result, the system has a good imaging quality and spectral detection capability. Also, the system can be used at 6000 m underwater, which may provide a new feasible technical scheme for deep-sea exploration.